1991
DOI: 10.1007/bf03346813
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to glibenclamide impairs insulin secretion in isolated rat pancreatic islets

Abstract: We investigated the effect of 24 h exposure to 100 nmol/l glibenclamide on insulin secretion in isolated rat pancreatic islets. The insulin content was similar in control islets and in islets preincubated with 100 nmol/l glibenclamide for 24 h. In islets preexposed to glibenclamide: 1) the subsequent response to a maximal glibenclamide stimulatory concentration (10 mumol/l, 1 h at 37 C) was greatly reduced in comparison to control islets (0.69 +/- 0.20% vs 2.16 +/- 0.41%; mean +/- SE; n = 14; p less than 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…This observation was confirmed using isolated perifused rat islets. Both tolbutamide and glibenclamide, however, increased insulin release in rat islets to levels comparable with those reported in other islet studies (Gullo et al 1991, Rabuazzo et al 1992. Our observation that among the sulphonylureas only glibenclamide is able to stimulate NPY release may be related to several possibilities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This observation was confirmed using isolated perifused rat islets. Both tolbutamide and glibenclamide, however, increased insulin release in rat islets to levels comparable with those reported in other islet studies (Gullo et al 1991, Rabuazzo et al 1992. Our observation that among the sulphonylureas only glibenclamide is able to stimulate NPY release may be related to several possibilities.…”
Section: Discussionsupporting
confidence: 89%
“…The cause of this 'secondary-failure' has been the subject of several investigations and have been ascribed to ' -cell exhaustion' (Schauder et al 1977, Gullo et al 1991, Rabuazzo et al 1992) and/or ' -cell desensitization' to glucose (Hoenig et al 1986, Bolaffi et al 1988, Purrello et al 1989 or other secretagogues (Grodsky 1989). An in vitro experiment (Gullo et al 1991) has shown that 24 h exposure of islets to 100 nmol/l glibenclamide did not deplete the insulin content, suggesting that mechanisms other than insulin depletion are operative which contribute to the reduced insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many patients, sulphonylureas effectively control glycaemia for an extended period [63], but over the long term (months to years), sulphonylurea therapies may fail [64]. Studies in normal rats [65][66][67], isolated normal islets [68] and cell lines [69] have shown that long-term glibenclamide treatment may impair glucose tolerance and GSIS. Our studies with chronic glibenclamide dosing of normal mice show an impaired secretory response that can be rapidly reversed following removal of the drug in vitro.…”
Section: 'Inverse U' Model For B-cell Response To Hyperexcitabilitymentioning
confidence: 99%
“…Insulin release during a 2-h static incubation in basal (3 mM) or high (12 mM) glucose was compared for the same experimental groups tested in the above electrophysiology studies. Because prolonged tolbutamide pretreatment to rescue mutant channel surface expression may desensitize cells to subsequent glucose stimulation by affecting their insulin secretory capacity (36,37) and confound data interpretation, we optimized the tolbutamide pretreatment such that no reduction in subsequent glucose stimulated insulin secretion was observed in uninfected control cells. We found that pretreating INS-1 cells with tolbutamide for 4 h rescued mutant surface expression without affecting insulin secretory capacity.…”
Section: Expression Of R74w or E128k Mutant Alters Ins-1 Cell Responsmentioning
confidence: 99%